New curricula and missed opportunities: Crowded curricula, connections, and ‘big ideas’ - Hurst, Chris (2015)
The recent review of Australian Curriculum represents an opportunity to significantly change the teaching of primary mathematics in Australia and perhaps elsewhere. The current curriculum document presents content in a linear and compartmentalized manner that dominates its structure and doesn’t explicitly accentuate the links and connections found in the ‘big ideas’ of mathematics. As well, it pays lip service to the ‘big process ideas’- the Proficiencies - which should be the vehicles for developing and making explicit links between and within the ‘big content ideas’. The nature of key content needs to be reconsidered and organised on the basis of the ‘big ideas’ of mathematics, and to emphasize the links and connections within and between them, as well as between them and real contexts. Such connections should be made explicit for children and hence teachers may need to hold their mathematical knowledge in different ways. The review document acknowledges the issue of the ‘crowded curriculum’ and makes recommendations such as increasing the depth of content whilst reducing its breadth. Exactly how this will be achieved remains to be seen but it is strongly suggested in this position paper that there needs to be a reorganization of content on the basis of ‘big ideas of mathematics’ or at least a substantial acknowledgement that this is important.